Planejamento e avalia??o de novos inibidores de Pteridina Redutase 1 (PTR1) de Leishmania major - Leite, Franco Henrique Andrade (2015)
According to WHO, Leishmaniasis is the second most important disease caused by protozoans. However, the available therapeutic arsenal for its treatment is limited and has low efficacy and safety profile. Once Leishmania ssp. are pteridine auxotrophs key enzymes of the folate metabolism have been targeted to circumvent this dilemma. However, Dihydrofolate Reductase-Thymidylate Synthase (DHFR-TS) inhibitors are ineffective against Leishmania major due to an alternative folate pathway regulated by Pteridine Reductase 1 (PTR1). Thus, identifying molecules that act on both enzymes is crucial to develop new leishmanicidal drugs. For that reason, the main goal of this study is to identify, through in silico approaches, (pharmacophore models), putative PTR1 inhibitors that also show structural requirements for L. major DHFR-TS inhibition. The pharmacophore models 10 and 20, PTR1 (2 H-bond donors, 4 H-bond acceptors and 3 hydrophobic centers) and DHFR-TS inhibitors (2 H-bond acceptors and 2 hydrophobic centers) respectively, show high performance to differentiate true-binders from decoys (AUCPTR1=0.90; AUCDHFR-TS=0.86) and to explain the structure-activity relationships for the inhibitors under study. Thus, these models were employed sequentially to select 10 molecules whose effect over the thermal stability of LmPTR1 was investigated by ThermoFluor?. According to this assay, two molecules stabilize LmPTR1: Z80393 (?Tm = 1.02?C) and Z33165 (?Tm = 0.9?C). Binding displacement assays with biopterin or NADPH showed that Z80393 binds within the substrate binding site, whereas Z33165 binds in the cofactor binding site. Z80303 effect over the catalytic activity of PTR1 was investigated by fluorimetry. This approach allowed us to determine the inhibitor?s potency (IC50=32.31 ? 1.18 ?M). Finally, Z80303 putative binding profile was generated by molecular docking and analyzed by Molecular Dynamics (productive phase= 15 ns). The results show that during 70% of the simulation, Z80393 H-bonds to Ser-111 and Arg-17 residues. Therefore, this study not only led to identification of a new class of LmPTR1 inhibitors, but also allowed us to determine its potency, mode of inhibition and binding profile towards its therapeutic target.